Smart Room Based on ESP32 and Google Assistant: Automation Solution in Electrical Engineering Laboratory Environment - Syamsuri, Wahyu; Wijanarko, Yudi; Maja, Ibnu (Internet of Things and Artificial Intelligence Journal, 2025)
The development of home automation technology and smart rooms is growing rapidly, especially through the utilization of voice commands to control electronic devices. This research develops a voice command-based smart room system using an ESP32 module connected with Google Assistant and the IFTTT platform for device control in an electrical engineering laboratory. The system allows users to turn on or off devices such as lights and TVs with just a voice, improving the efficiency and convenience of laboratory operations. The implementation using ESP32 as a Wi-Fi microcontroller, which activates relays to control devices, was tested in real laboratory conditions that have challenges in the form of electromagnetic interference and noise. The test results showed a fast and accurate system response of up to 90%, although there were some failures in high noise conditions. The system has the potential to be an effective automation solution to support learning and practical processes in electrical engineering laboratories, with further development needed to improve the system's robustness against noise interference.